THE STRATEGY OF URBAN RECOMPOSITION AS AN ANSWER TO THE DIFFICULTIES OF THE EXTENSION OF THE CITY OF ANNABA. - Abboud, Omar; BENMISSI , Ahcene (Journal of Human Sciences, 2020)
Our scientific participation tries to study the quality of morphological transformations in the city of Annaba, which seeks the improvement of its image in order to strengthen its strategic position as a metropolis. While, faced with the difficulties of its extension, and by the in-depth study of transformations in the centre. We are thinking of the importance of the urban recomposition strategy that will ensure the valorization and prosperity of its urban fabric, in a context of sustainability and cooperation between all actors.